INTEGRATED STRATIGRAPHY OF THE LOWER AND MIDDLE FERNIE FORMATION IN ALBERTA AND BRITISH COLUMBIA, WESTERN CANADA - RUSSELL HALL; VICKI MCNICOLL; DARREN GRÖCKE; JAMES CRAIG; KEVIN JOHNSTON (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
The lower and middle parts of the Fernie Formation in central-western Alberta and south-eastern British Columbia, ranging from Pliensbachian to ?Bathonian (Early to Middle Jurassic) in age, and consisting mainly of fossiliferous dark shales and black limestones, contain bentonitic clay horizons which have yielded radiometric ages using U-Pb analysis of zircon crystals. Here we report six new ages from the lowermost Red Deer Member (188.3 +1.5/-1 Ma); Highwood Member (ca. 173 Ma and 166.6 ± 0.2 Ma); and Grey Beds (167.0 ± 0.2 Ma, 165.6 ± 0.3 Ma, and 165.4 ± 0.3 Ma). Some of these bentonites are associated with ammonites and coccoliths which provide biostratigraphic constraints. Strontium and carbon and oxygen isotopes measured from belemnite rostra have been compared in two sections and the resulting curves are compared with those from western Europe.